PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Cabang Pandanaran) - Junistyaningrum, Nurulita; Sugiarto, Yohanes (Diponegoro Journal of Management, 2016)
This research examines two independent variables that is Building Service Partnership--of which the dependent variable of Customer Loyalty can be influenced--and Customer Satisfaction as the interverning variable. The direct coefficient determination (R2) test results 22,7%, meanwhile a 30,0% derived from the indirect coefficient determination (R2) test. In the other hand, testing hypotheses concerning partial correlation confirms that (i) Building Service Partnership indicates a positive and significant relationship towards Customer Satisfaction; (ii) Total Quality Management indicates a positive and significant relationship towards Customer Satisfaction; (iii) Building Service Partnership indicates a positive and significant relationship towards Customer Loyalty; (iv) Total Quality Management indicates a positive and significant relationship towards Customer Loyalty; and (v) Customer Satisfaction indicates a positive and significant relationship towards Customer Loyalty. From the significant hypothesis test (F-test), it can be derived that there is positive and significant influence between Building Service Partnership and Total Quality Management towards Customers Loyalty, with Customer Satisfaction as its interverning variable.